Sid Meier’s Civilization VI as a Potential Teaching Aid. Possibilities and Threats - Theoretical Remarks - Lis, Tymoteusz (Sensus Historiae, 2025)
In an increasingly digitised world, which is primarily oriented towards iconographic content, it often becomes indispensable to look for new forms and didactic aids that can not only tell, but also show history in an interesting way. This paper is an attempt to present one of the best-known and best-loved strategy video games - Sid Meier’s Civilization VI - in just such a context. The interface and mechanics of the game are analysed in order to demonstrate the extent of its usefulness as a potential teaching aid. By explicitly pointing out the multitude of possibilities and possible dangers, together with their exemplary solution, the work is a theoretical introduction and a kind of ‘guide’ to its possible use in school practice